AN ANALYSIS OF EFFECTIVENESS AND EFFICIENCY BUDGET REALIZATION AS PERFORMANCE MEASUREMENT POLYTECHNIC MEDAN - Vina Wani Nasution; Rahima Br. Purba (SEAN Institute, 2022)
Society in the modern era demands a clean government or good government that can provide accountable and transparent information in its financial management. Budgets managed by public sector organizations must apply the principles of efficiency and effectiveness which are indicators of the financial performance of a public sector entity. This study aims to determine the effectiveness and efficiency of the budget at the Medan State Polytechnic, for the 2019-2021 budget period. The research method used is quantitative descriptive analysis. Data collection techniques used are observation techniques, interviews, and literature study. The data analysis method used is the calculation of the measurement of effectiveness and efficiency. The results of this study indicate that the level of effectiveness in 2019-2021 is stated to be effective and the level of efficiency from 2019-2021 is overall very efficient. It is hoped that the Medan State Polytechnic will further improve the efficiency of the spending budget, requiring better coordination and budget preparation strategies as well as the implementation of budget realization.